Tau, Amyloid, and Hypometabolism in a Patient with Posterior Cortical Atrophy - Ossenkoppele, Rik (Ann Neurol, 2014)
Determining the relative contribution of amyloid plaques and neurofibrillary tangles to brain dysfunction in Alzheimer disease is critical for therapeutic approaches, but until recently could only be assessed at autopsy. We report a patient with posterior cortical atrophy (visual variant of Alzheimer disease) who was studied using the novel tau tracer [(18)F]AV-1451 in conjunction with [(11)C]Pittsburgh compound B (PIB; amyloid) and [(18)F]fluorodeoxyglucose (FDG) positron emission tomography. Whereas [(11)C]PIB bound throughout association neocortex, [(18)F]AV-1451 was selectively retained in posterior brain regions that were affected clinically and showed markedly reduced [(18)F]FDG uptake. This provides preliminary in vivo evidence that tau is more closely linked to hypometabolism and symptomatology than amyloid.